Biomechanics of slalom water skiing - Bray-Miners, J.; Runciman, R. J.; Monteith, G.; Groendyk, N. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
Water skiing has received little attention in research literature and has not utilized recent advancements in analysis technology like other highly dynamic sports. In this study, six advanced slalom skiers were recruited to test four different high-performance ski designs, with the goal being to detect performance differences achieved between ski designs and between skiers during slalom turns. To aid the analysis of the resulting activity data, a series of 11 quantitative performance parameters were defined and studied. Instrumentation included a skier-mounted, wireless, Global Positioning System sensor providing instantaneous skier velocity, a uniaxial force transducer providing rope load, and a wireless, inertial measurement unit attached to the skis to provide ski roll, ski acceleration and deceleration. Statistical analysis suggested that there was a difference in the average peak roll achieved between the skis, but was unable to suggest a difference between skis in the other performance parameters. In contrast, however, statistical analysis indicated that there was a difference in the performance achieved between the skiers, which is supported by their slalom course success rates. The identified performance parameters were effective at differentiating skier ability levels with the subject with the highest success rate among the top three highest scoring for 10 of 11 parameters and the subject with the lowest success rate was among the bottom 2 in all 11 parameters.